Corporate Social Responsibility and Regulatory Governance
XV, 309 p.
Keywords: This is the first of two volumes that examine the changing nature of state-business relations. This book assesses the potential and limits of CSR in developing countries, by focusing on aspects that are often ignored in the CSR literature: historical experience, theoretical perspectives, and institutional and political dimensions of change.